PERAN INFRASTRUKTUR TEKNOLOGI INFORMASI DALAM MENDUKUNG PENGELOLAAN INFORMASI KEUANGAN DI ERA CLOUD COMPUTING - Nazla Alifia Putri Hadi; Imelda Malona Tarigan (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the role of information technology infrastructure in supporting financial information management in the era of cloud computing. The study employs a qualitative method with a descriptive approach through a literature review sourced from relevant books, journals, and scientific articles. The analysis examines various concepts and research findings related to information technology infrastructure, financial information management, and cloud computing. The results indicate that information technology infrastructure comprising hardware, software, communication networks, databases, and cloud computing services plays a crucial role in enhancing the speed, accuracy, integration, and accessibility of financial information. The adoption of cloud computing also offers benefits such as operational cost efficiency, real-time data access, improved collaboration, and support for more effective managerial decision-making. However, its implementation still faces challenges such as data security risks, cyber threats, dependence on internet connectivity, and human resource readiness. This study concludes that information technology infrastructure and cloud computing are key factors in improving the effectiveness and quality of financial information management in the digital era.